Functional Movement Screen Task Scores and Joint Range-of-motion: A Construct Validity Study - Hincapié, Cesar A.; Tomlinson, George A.; Hapuarachchi, Malinda; Stankovic, Tatjana; Hirsch, Steven; Carnegie, Danielle; Richards, Doug; Frost, David; Beach, Tyson A.C. (International Journal of Sports Medicine, 2022)
Little is known about the construct validity of the Functional Movement Screen (FMS). We aimed to assess associations between FMS task scores and measures of maximum joint range-of-motion (ROM) among university varsity student-athletes from 4 sports (volleyball, basketball, ice hockey, and soccer). Athletes performed FMS tasks and had their maximum ankle, hip and shoulder ROM measured. Multivariable linear regression was used to estimate associations between FMS task scores and ROM measurements. 101 university student-athletes were recruited (52 W/49 M; mean age 20.4±1.9 years). In general, athletes with higher FMS task scores had greater ROM compared to those with lower task scores. For example, athletes who scored 2 on the FMS squat task had 4° (95% CI, 1° to 7°) more uni-articular ankle dorsiflexion ROM compared with those who scored 1, while those who scored 3 on the FMS squat task had 10° (4° to 17°) more uni-articular ankle dorsiflexion ROM compared with those who scored 1. Large variation in ROM measurements was observed. In sum, substantial overlap in joint ROM between groups of athletes with different FMS task scores weakens the construct validity of the FMS as an indicator of specific joint ROM.
Keywords: construct validity; functional movement screen; measurement; mobility; range-of-motion; stability